Assessment of Quality of Life in Advanced-Stage Lung Cancer Patients Using EORTC QLQ-C30 Questionnaire - Ariantika, Ariantika; Lubis, Rahayu; Asfriyati, Asfriyati; Ashar, Taufik; Nurmaini, Nurmaini; Soeroso, Noni Novisari; Siregar, Kamal Basri; Lim, Darren Wan-Teck (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Quality of life (QoL) is a multidomain concept that assesses a person through health status, functional status, and symptoms. The patient's QoL is greatly reduced due to the course of disease, severity of symptoms, and side effects of chemotherapy treatment. This study aimed to assess the QoL in advanced lung cancer patients using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 (EORTC QLQ-C30). Methods: This descriptive and observational study was conducted at the Pulmonary Polyclinic, Prof. Dr. Chairuddin Panusunan Lubis Universitas Sumatera Utara (USU) Hospital from February to July 2024, with a cross-sectional design using patient medical records and EORTC QLQ-C30 questionnaire. The EORTC QLQ-C30 questionnaire was analyzed with a score formula and categorized as good, moderate, and bad. The sample was 100 lung cancer patients using a purposive sampling technique according to the criteria. Results: The results showed that almost all QoL was in the moderate category (80%). The general health status was mostly in the moderate category (61.66%), the functional status was mostly in the good category (75.35%), and the symptoms were in the moderate category (35.65%). In the functional scale, the role domain had the lowest mean, 69.99 ± 29.43. In the symptoms scale, the pain domain had the highest mean, 52.66 ± 29.43. Conclusion: The overall QoL of lung cancer patients was in the moderate category, lower than the healthy population. It needs to be improved, especially in the role domain, by providing supportive-expressive group therapy.